3D covalent organic framework for morphologically induced high-performance membranes with strong resistance toward physical aging - Yang, Yanqin (2021)
The physicochemical properties of filler materials are critical considerations influencing the separation performances of mixed-matrix membranes (MMMs). Herein, a three-dimensional covalent organic framework (3D-COF) with a secondary amine-containing backbone was designed to offer large surface area, high porosity and good affinity toward CO2 molecules. Membranes prepared from this 3D-COF filler and a 6FDA-DAM polyimide matrix demonstrated a more significant enhancement in the CO2/CH4 separation performance, which was unattainable by its 2D-COF analogue. Specifically, with 10 and 15 wt% loadings of 3D-COF fillers, the MMMs membranes were able to enhance the CO2 permeability by ~57% and 140%, respectively, at a comparable, if not better, CO2/CH4 selectivity than the unfilled membrane. Furthermore, glassy polymers of high fractional free volume such as 6FDA-DAM tend to suffer from a ubiquitous loss in performance over time due to a physical aging effect. In this regard, the 3D-COF was effective in slowing down the aging process by capitalizing on its high surface area and amine functional groups to immobilize and rigidify the 6FDA-DAM polymer chains, preventing the collapse of the free volume. This allows 97% of the initial membrane performances to be effectively retained after 240 days of aging. Our findings suggest the potential of morphologically-tuned COFs to develop high-performance MMMs with strong practical relevance.